Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1097/00140068-200301001-00003
|View full text |Cite
|
Sign up to set email alerts
|

Can Variability in Corneal Metabolism Explain the Variability in Corneal Swelling?

Abstract: Corneal swelling is associated with corneal metabolic activity and endothelial function; however, other factors must also be involved. Contact lens wearers do not adapt by modifying oxygen consumption but probably by using glucose more efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…It has been reported that both the metabolic activity and the endothelial function are two factors that contribute to corneal swelling. 23,57 The interaction of these and other factors in the recovery from edema may occur to different extents between subjects and at different time points after removal of the hypoxic stimulus for each subject, resulting in a lack of systematic behavior for the group over time. A third and related possibility is that the En-DM complex response is more dynamic than the biphasic changes observed in other layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both the metabolic activity and the endothelial function are two factors that contribute to corneal swelling. 23,57 The interaction of these and other factors in the recovery from edema may occur to different extents between subjects and at different time points after removal of the hypoxic stimulus for each subject, resulting in a lack of systematic behavior for the group over time. A third and related possibility is that the En-DM complex response is more dynamic than the biphasic changes observed in other layers.…”
Section: Discussionmentioning
confidence: 99%
“…22 The rate of recovery of hypoxia-induced edema is thought to represent the endothelial pump function. [23][24][25] In humans, extended eye closure during contact lens wear is an effective model of hypoxia and has been used often to model the normal physiological response of the cornea 8,26 as well as in altered conditions in postsurgical [27][28][29] and lenswearing 24 patients.…”
mentioning
confidence: 99%
“…It may not be feasible to control for all possible individual differences that could possibly impact the CS in a single study. However, based on the literature, [28][29][30][31] we suggest adding individual measures of corneal oxygen demand (corneal Mixed Modeling of Between-Subject Corneal Swelling IOVS j May 2018 j Vol. 59 j No.…”
Section: Discussion Random Individual Contributions To Corneal Swellingmentioning
confidence: 99%
“…An important effect of the use of contact lenses is corneal swelling or edema, which can affect visual quality and visual acuity if large enough. Bonanno et al (38) concluded that corneal swelling is related to metabolic activity and endothelial function; however, other factors could also be involved, which may include physical forces, interlamellar tightness, or circumlimbal clamping. Changes in corneal thickness caused by these soft contact lenses under study are not clinically significant, since all the lenses introduced changes below 1.9% in central and peripheral corneal thickness, and Hess and Garner (39) stated that visual function is slightly compromised when the change in corneal thickness is about 6%.…”
Section: Discussionmentioning
confidence: 99%